Effects of Antidepressants on Sleep - Wichniak, Adam; Wierzbicka, Aleksandra; Walęcka, Małgorzata; Jernajczyk, Wojciech (Current psychiatry reports, 2017)
Purpose of Review The aim of this review article was to summarize recent publications on effects of antidepressants on sleep and to show that these effects not only depend on the kind of antidepressant drugs but are also related to the dose, the time of drug administration, and the duration of the treatment. Recent Findings Complaints of disrupted sleep are very common in patients suffering from depression, and they are listed among diagnostic criteria for this disorder. Moreover, midnocturnal insomnia is the most frequent residual symptom of depression. Thus, all antidepressants should normalize sleep. However, at least in short-term treatment, many antidepressants with so-called activating effects (e.g. fluoxetine, venlafaxine) may disrupt sleep, while others with sedative properties (e.g., doxepin, mirtazapine, trazodone) rapidly improve sleep, but may cause problems in long-term treatment due to oversedation.For sleep-promoting action, the best effects can frequently be achieved with a very low dose, administered early enough before bedtime and importantly, always as a part of more complex interventions based on the cognitive-behavioral protocol to treat insomnia (CBT-I). Summary For successful treatment of depression, it is necessary to understand the effects of antidepressants on sleep. Each physician should also be aware that some antidepressants may worsen or induce primary sleep disorders like restless legs syndrome, sleep bruxism, REM sleep behavior disorder, nightmares, and sleep apnea, which may result from an antidepressant-induced weight gain.